Degradable epoxy resin composition, cured product and application thereof

The degradable epoxy resin composition formed by reacting oxalic acid polyester polyol with an ester-containing bond epoxy resin under a cationic initiator solves the problem that existing epoxy resin cured substances are difficult to degrade and recover, and achieves low energy consumption and low The rapid degradation effect of cost is suitable for high-end applications and naturally degraded in seawater.

CN119463115AActive Publication Date: 2025-02-18NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411803355.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-18
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing cured epoxy resins are difficult to degrade and recover, resulting in waste of resources and environmental pollution. The energy consumption of the dynamic covalent chemical degradation process is high, hindering the widespread application of degradable resins in the industrial field.

Method used

The oxalic acid polyester polyol and the ester-containing bonded epoxy resin undergo an open-loop chain transfer reaction in the presence of a cationic initiator to form a degradable epoxy resin composition, and its cured substance can rapidly degrade in low-concentration alkaline aqueous solution or seawater. .

Benefits of technology

It realizes low energy consumption and low cost degradation of epoxy resin, is suitable for high-end application fields, and achieves natural degradation in seawater, solving the problems of resource waste and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463115A_ABST
    Figure CN119463115A_ABST
Patent Text Reader

Abstract

The invention provides a degradable epoxy resin composition, a cured product and application thereof. The degradable epoxy resin composition comprises oxalic acid polyester polyol, ester bond-containing epoxy resin and a cationic initiator, wherein the mass ratio of the oxalic acid polyester polyol to the ester bond-containing epoxy resin to the cationic initiator is (20-50): (50-80): (5-10); the structure of the oxalic acid polyester polyol is as shown in a formula I: # imgabs0 #, wherein R1 and R2 are independently selected from C2-C12 aliphatic chain groups or aliphatic ring groups. A condensate formed by the degradable epoxy resin composition has excellent degradability, can be degraded in a low-concentration alkaline aqueous solution or seawater, and also has good thermodynamic properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermosetting resins, and in particular relates to a degradable epoxy resin composition, a degradable epoxy resin cured product and applications thereof. Background Art

[0002] Epoxy resin is one of the important thermosetting resins. Due to its excellent bonding properties, electrical insulation properties, chemical stability and mechanical properties, it has been widely used in automobile manufacturing, aerospace, wind power generation and electrical appliances. However, ordinary epoxy resin cured products cannot be reprocessed by heating and melting or solvent dissolution, and are even more difficult to degrade and recycle. After being discarded, they can only be disposed of by landfill, crushing, strong oxidation, strong acid / alkali degradation, etc., which not only wastes resources but also brings serious environmental pollution problems. In recent years, the mild degradation and recycling of epoxy resins have become an important research direction and have received widespread attention from academia and industry.

[0003] Current research has found that based on dynamic covalent chemistry, epoxy resin can be degraded under specific stimulation conditions (such as heating, light, pH or catalyst, etc.), thereby realizing the recycling of epoxy resin. Inspired by this, domestic and foreign scholars have introduced dynamic covalent bonds into the cross-linked network of epoxy resin and prepared a series of new materials with excellent degradation performance. However, the current degradation process of epoxy resin using dynamic bonds often consumes a large amount of solvent and can only be carried out at a specific temperature, which leads to relatively high energy consumption in the degradation process, hindering the widespread application of degradable resins in the industrial field. Summary of the invention

[0004] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0005] One of the purposes of the present invention is to provide a degradable epoxy resin composition, which comprises oxalic acid polyester polyol, ester bond-containing epoxy resin and cationic initiator, wherein the mass ratio of oxalic acid polyester polyol, ester bond-containing epoxy resin and cationic initiator is 20-50:50-80:5-10;

[0006] The structure of the oxalic acid polyester polyol is shown in Formula I:

[0007]

[0008] Wherein, R1 and R2 are independently selected from C2-C 12 aliphatic chain group or aliphatic ring group.

[0009] The present invention takes carbon dioxide compound oxalic acid as a starting point, and utilizes oxalic acid polyester polyol and ester bond epoxy resin to be able to undergo ring-opening chain transfer reaction under the condition of cationic initiator to obtain a series of degradable epoxy resin compositions. The oxalate structure in the oxalic acid polyester molecular segment has a special adjacent carbonyl structure, which has a strong electron-withdrawing effect, thereby being endowed with excellent degradation ability. The epoxy resin containing ester bond is copolymerized with oxalate, and a cross-linked network system containing different ester bonds is obtained at the same time, and the degradation of oxalate will drive the degradation of other types of ester bonds. Therefore, the cured product of the resin composition can be degraded in a low-concentration alkaline aqueous solution, and can also achieve natural degradation in seawater, with excellent degradable performance. In addition, the cured product of the resin composition has excellent thermodynamic properties, and is suitable for high-end application fields that require high strength and rapid degradation of polymer materials.

[0010] In some embodiments, the molecular weight of the oxalic acid polyester polyol is 2000-50000 g / mol.

[0011] In some typical embodiments, the oxalic acid polyester polyol includes one or more combinations of the following compounds I-1, I-2, I-3, I-4, I-5, and I-6, but is not limited thereto:

[0012]

[0013] In some embodiments, the ester bond-containing epoxy resin includes an epoxy resin having a structure shown in Formula II and / or an epoxy resin having a structure shown in Formula III:

[0014]

[0015] Among them, V and Y are C2-C 12 Aliphatic chain group or aliphatic ring group.

[0016] In some embodiments, the ester bond-containing epoxy resin includes one or more of the following epoxy resins II-1, II-2, II-3, III-1, and III-2, but is not limited thereto:

[0017]

[0018] In some embodiments, the cationic initiator includes a cationic photoinitiator and / or a cationic thermal initiator.

[0019] In some embodiments, the cationic photoinitiator includes one or a combination of multiple of diazonium salts, diaryliodonium salts, triarylsulfonium salts, alkylsulfonium salts, iron arene salts, sulfonyloxy ketones or triarylsiloxane ethers, but is not limited thereto.

[0020] In some embodiments, the cationic thermal initiator includes one or a combination of multiple of antimonates, phosphates, alkylammonium salts, aryldiazonium salts or onium salts, but is not limited thereto.

[0021] The second object of the present invention is to provide the use of the degradable epoxy resin composition in the preparation of wind power composite materials, electronic consumer products, electronic packaging or electrical resins.

[0022] The third object of the present invention is to provide a degradable epoxy resin cured product, wherein the degradable epoxy resin cured product is formed by thermal curing or photocuring of the degradable epoxy resin composition.

[0023] In some embodiments, the thermal curing method comprises: curing the degradable epoxy resin composition at a temperature of 50 to 100° C. for 3 to 6 hours.

[0024] In some embodiments, the photocuring method comprises: irradiating the degradable epoxy resin composition under ultraviolet light for 5 to 10 minutes. The ultraviolet light is, for example, 365 nm ultraviolet light.

[0025] In some embodiments, the degradable epoxy resin cured material can be degraded in an alkaline aqueous solution or seawater; in an alkaline aqueous solution at 25 to 100°C, the degradation rate of the degradable epoxy resin cured material within 2 to 48 hours is ≥99%; in seawater at 25°C, the degradation rate of the degradable epoxy resin cured material within 300 to 900 days is ≥99%.

[0026] In some embodiments, the glass transition temperature of the degradable epoxy resin cured product is 50-150°C, the tensile strength is 50-110 MPa, and the unnotched impact strength is 30-60 kJ / m 2 .

[0027] A fourth object of the present invention is to provide a device with a degradable structure, wherein the degradable structure of the device includes the degradable epoxy resin cured product.

[0028] A fifth object of the present invention is to provide a method for degrading a degradable epoxy resin cured product, comprising: immersing the degradable epoxy resin cured product in an alkaline solution to degrade it, or placing it in seawater for natural degradation.

[0029] In some embodiments, the pH value of the alkaline solution is 9-14.

[0030] In some embodiments, the soaking time in the alkaline solution is 2 to 48 hours.

[0031] In some embodiments, the temperature of the alkaline solution is above 25°C, preferably 25-100°C.

[0032] Compared with the prior art, the present invention has at least the following beneficial effects:

[0033] (1) The present invention uses carbon dioxide compound oxalate as a starting point, and utilizes oxalic acid polyester polyol and ester-bond epoxy resin to undergo a ring-opening chain transfer reaction in the presence of a cationic initiator to obtain a series of degradable epoxy resin compositions. The cured resin material has both excellent thermodynamic properties and degradability, and is suitable for use in high-end application fields that require high strength and rapid degradation of polymer materials.

[0034] (2) Compared with other degradable epoxy resin systems containing dynamic bonds, oxalate has the advantages of low price, abundant sources and simple synthesis process, so the preparation cost of the resin composition is low; based on the excellent degradation performance of the degradable epoxy resin, it can be degraded in a relatively low concentration alkaline solution and a relatively mild temperature condition, and the required degradation time is relatively short; or it can be naturally degraded by utilizing abundant seawater resources, and basically no other energy consumption is required, thus solving the problem of high energy consumption and resource waste required for degrading epoxy resin in the prior art;

[0035] (3) The preparation method of the resin composition provided by the present invention is simple, easy to operate, the reaction conditions are controllable, easy to implement, and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is the NMR spectrum of the oxalic acid polyester polyol used in the degradable resin composition in Example 1 of the present invention.

[0038] Figure 2 This is the NMR spectrum of the oxalic acid polyester polyol used in the degradable resin composition in Example 2 of the present invention.

[0039] Figure 3 This is the NMR spectrum of the oxalic acid polyester polyol used in the degradable resin composition in Example 3 of the present invention. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0041] In addition, unless otherwise specified, the various raw materials used in the following examples can be purchased from the market and other channels, and the various production and testing equipment used are also equipment known in the art.

[0042] In the specific embodiment of the present invention, the test method for the glass transition temperature of the degradable epoxy resin cured product is based on ASTM E1545-22; the tensile strength test method is based on GB / T 2567-2021; and the unnotched impact strength test method is based on GB / T2567-2021.

[0043] The test method for the degradation rate of degradable epoxy resin cured product in alkaline aqueous solution and seawater is as follows: grind the above cured product into powder, then put it into alkaline solution or seawater for degradation reaction, filter the solution after the degradation is completed, dry the filter cake, and analyze the degradation rate of the cured powder. Degradation rate (%) = (1-mass of the dried filter cake / mass of the cured powder) * 100%).

[0044] The oxalic acid polyester polyol used in the following specific embodiments is prepared with reference to the prior art CN202111088640.9.

[0045] Example 1

[0046] This embodiment provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and iron aromatic salt photoinitiator (I-261) in a mass ratio of 20:80:5;

[0047] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0048]

[0049] Figure 1 is the NMR spectrum of the oxalic acid polyester polyol used in this embodiment;

[0050] The structure of the epoxy resin used in this embodiment is as follows:

[0051]

[0052] The degradable epoxy resin composition was irradiated under 365 nm ultraviolet light for 10 minutes to obtain a degradable epoxy resin cured product.

[0053] The relevant properties of the prepared epoxy resin cured product were tested. The results showed that the glass transition temperature of the degradable epoxy resin cured product was 115°C, the tensile strength was 58MPa, and the unnotched impact strength was 40kJ / m 2 , in an alkaline aqueous solution of 0.5 M OH at 35 °C - The degradation rate is 99% within 48 hours in water at 25°C, and reaches 99% within 198 days in seawater at 25°C.

[0054] Example 2

[0055] The present embodiment provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and diaryl iodonium salt photoinitiator (4,4'-diacetamidophenyl iodonium hexafluorophosphate) in a mass ratio of 30:70:6.

[0056] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0057]

[0058] Figure 2 is the NMR spectrum of the oxalic acid polyester polyol used in this embodiment;

[0059] The structure of the epoxy resin used in this embodiment is as follows:

[0060]

[0061] The degradable epoxy resin composition was irradiated under 365 nm ultraviolet light for 8 minutes to obtain a degradable epoxy resin cured product.

[0062] The relevant properties of the prepared epoxy resin cured product were tested. The test results showed that the glass transition temperature of the degradable epoxy resin cured product was 112°C, the tensile strength was 65MPa, and the unnotched impact strength was 45kJ / m 2 , in an alkaline aqueous solution of 0.2 M OH at 85 °C - The degradation rate is 99% within 24 hours in seawater at 25°C, and reaches 99% within 275 days in seawater at 25°C.

[0063] Example 3

[0064] This embodiment provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and iron aromatic salt photoinitiator (I-262) in a mass ratio of 40:60:10.

[0065] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0066]

[0067] Figure 3 is the NMR spectrum of the oxalic acid polyester polyol used in this embodiment;

[0068] The epoxy resin structure used in this embodiment is as follows:

[0069]

[0070] The degradable epoxy resin composition was irradiated under 365 nm ultraviolet light for 5 minutes to obtain a degradable epoxy resin cured product.

[0071] The relevant properties of the prepared biodegradable epoxy resin cured product were tested. The test results showed that the glass transition temperature of the biodegradable epoxy resin cured product was 102°C, the tensile strength was 71MPa, and the unnotched impact strength was 55kJ / m 2 , in an alkaline aqueous solution of 1.0 M OH at 25 °C - The degradation rate is 99% within 48 hours in water at 25°C, and reaches 99% within 298 days in seawater at 25°C.

[0072] Example 4

[0073] Example 4 provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and triarylsulfonium salt photoinitiator (S-phenyl-S-(2-benzoxazole)-S-[4-(S-2-benzopurazole)phenyl]sulfur trifluoromethanesulfonate) in a mass ratio of 35:75:5.

[0074] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0075]

[0076] The epoxy resin structure used in this embodiment is as follows:

[0077]

[0078] The degradable epoxy resin composition was irradiated under 365 nm ultraviolet light for 10 minutes to obtain a degradable epoxy resin cured product.

[0079] The relevant properties of the degradable epoxy resin cured product were tested, and the test results showed that the glass transition temperature of the degradable epoxy resin cured product was 136°C, the tensile strength was 75MPa, and the unnotched impact strength was 52kJ / m 2 , in an alkaline aqueous solution of 0.9 M OH at 100 °C - The degradation rate is 99% within 24 hours in seawater at 25°C, and reaches 99% after 600 days in seawater at 25°C.

[0080] Example 5

[0081] The present embodiment provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and alkyl ammonium salt thermal initiator (alkyl dimethyl ammonium chloride) in a mass ratio of 30:70:5.

[0082] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0083]

[0084] The epoxy resin structure used in this embodiment is as follows:

[0085]

[0086] The degradable epoxy resin composition was cured at 80° C. for 6 hours to obtain a degradable epoxy resin cured product.

[0087] The relevant properties of the prepared biodegradable epoxy resin cured product were tested. The test results showed that the glass transition temperature of the biodegradable epoxy resin cured product was 116°C, the tensile strength was 69MPa, and the unnotched impact strength was 57kJ / m 2 , in an alkaline aqueous solution of 0.8 M OH at 100 °C - The degradation rate is 99% in 40 hours in seawater at 25°C, and reaches 99% in 850 days.

[0088] Example 6

[0089] This embodiment provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and antimonate thermal initiator (N-benzylpyrazine hexafluoroantimonate) in a mass ratio of 40:60:8.

[0090] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0091]

[0092] The structure of the epoxy resin used in this embodiment is as follows:

[0093]

[0094] The degradable epoxy resin composition was cured at 90° C. for 4 hours to obtain a degradable epoxy resin cured product.

[0095] The relevant properties of the prepared epoxy resin cured product were tested. The test results showed that the glass transition temperature of the degradable epoxy resin cured product was 85°C, the tensile strength was 62MPa, and the unnotched impact strength was 49kJ / m2 , in an alkaline aqueous solution of 1.0 M OH at 65 °C - The degradation rate is 99% within 48 hours in seawater at 25°C, and reaches 99% within 360 days.

[0096] Example 7

[0097] Example 7 provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and triarylsulfonium salt photoinitiator (S-phenyl-S-(2-benzoxazole)-S-[4-(S-2-benzopurazole)phenyl]sulfur trifluoromethanesulfonate) in a mass ratio of 35:75:5.

[0098] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0099]

[0100] The epoxy resin structure used in this embodiment is as follows:

[0101]

[0102] The degradable epoxy resin composition was irradiated under 365 nm ultraviolet light for 10 minutes to obtain a degradable epoxy resin cured product.

[0103] The relevant properties of the degradable epoxy resin cured product were tested, and the test results showed that the glass transition temperature of the degradable epoxy resin cured product was 86°C, the tensile strength was 52MPa, and the unnotched impact strength was 60kJ / m 2 , in an alkaline aqueous solution of 0.2 M OH at 100 °C - The degradation rate is 99% in 48 hours in water at 25°C, and reaches 99% in 900 days in seawater at 25°C.

[0104] Example 8

[0105] This embodiment provides a degradable epoxy resin composition, which is obtained by uniformly mixing oxalic acid polyester polyol, epoxy resin and antimonate thermal initiator (N-benzylpyrazine hexafluoroantimonate) in a mass ratio of 40:60:8.

[0106] The structure of the oxalic acid polyester polyol used in this embodiment is as follows:

[0107]

[0108] The structure of the epoxy resin used in this embodiment is as follows:

[0109]

[0110] The degradable epoxy resin composition was cured at 80° C. for 6 hours to obtain a degradable epoxy resin cured product.

[0111] The relevant properties of the prepared epoxy resin cured product were tested. The test results showed that the glass transition temperature of the degradable epoxy resin cured product was 121°C, the tensile strength was 81MPa, and the unnotched impact strength was 41kJ / m 2 , in an alkaline aqueous solution of 1.0 M OH at 85 °C - The degradation rate is 99% in 48 hours in water at 25°C, and reaches 99% in 900 days in seawater at 25°C.

[0112] Comparative Example 1

[0113] In Comparative Example 1, commercial polyester polyol (hexylene glycol adipate), epoxy resin and diazonium fluoroborate initiator were mixed in a mass ratio of 20:80:5 to obtain an epoxy resin composition.

[0114] The structure of the epoxy resin used in Comparative Example 1 is as follows:

[0115]

[0116] The epoxy resin composition was irradiated under 365 nm ultraviolet light for 10 minutes to obtain an epoxy resin cured product.

[0117] The relevant properties of the epoxy resin cured product were tested in the same manner as in Example 1. The test results showed that the glass transition temperature of the epoxy resin cured product was 105°C, the tensile strength was 51 MPa, and the unnotched impact strength was 37 kJ / m 2 The degradation rate is 0% within 48 hours in 1.0M OH alkaline aqueous solution at 25°C, and the degradation rate is 0% within 900 days in seawater at 25°C.

[0118] Comparative Example 2

[0119] The difference between Comparative Example 2 and Example 1 is that the epoxy resin used in Comparative Example 2 is an epoxy resin without ester bonds, specifically bisphenol A epoxy resin E51. The rest is the same as Example 1. The relevant properties of the epoxy resin cured product are: the glass transition temperature of the epoxy resin cured product is 95°C, the tensile strength is 61MPa, and the unnotched impact strength is 30kJ / m 2 , in an alkaline aqueous solution of 0.5 M OH at 35 °C - The degradation rate is 40% within 48 hours in water at 25°C, and 25% within 198 days in seawater at 25°C.

[0120] Compared with Example 1 and Example 2, the epoxy resin cured product prepared by using the ester bond-containing epoxy resin contains more ester bonds, which can make the cured product have a faster degradation rate and more thorough degradation.

[0121] In summary, the present invention utilizes the unique degradation characteristics of oxalate structure to develop a series of novel degradable epoxy resin compositions, which can not only achieve natural degradation in seawater, but also rapidly decompose in a low-concentration alkaline aqueous solution environment. The resin composition has broad application prospects in the fields of composite materials and encapsulation resins, indicating that the practical application of degradable epoxy resins will enter a new stage of development, and is expected to truly promote this field towards a more environmentally friendly and sustainable direction.

[0122] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0123] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0124] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A degradable epoxy resin composition, characterized in that: It comprises oxalic acid polyester polyol, ester bond-containing epoxy resin and cationic initiator, wherein the mass ratio of oxalic acid polyester polyol, ester bond-containing epoxy resin and cationic initiator is 20-50:50-80:5-10; The structure of the oxalic acid polyester polyol is shown in Formula I: Wherein, R1 and R2 are independently selected from C2-C 12 aliphatic chain group or aliphatic ring group.

2. The degradable epoxy resin composition according to claim 1, characterized in that: The molecular weight of the oxalic acid polyester polyol is 2000-50000 g / mol.

3. The degradable epoxy resin composition according to claim 1, characterized in that: The ester bond-containing epoxy resin includes an epoxy resin having a structure shown in Formula II and / or an epoxy resin having a structure shown in Formula III: Among them, V and Y are C2-C 12 Aliphatic chain group or aliphatic ring group.

4. The degradable epoxy resin composition according to claim 1, characterized in that: The cationic initiator includes a cationic photoinitiator and / or a cationic thermal initiator.

5. The degradable epoxy resin composition according to claim 4, characterized in that: The cationic photoinitiator includes one or more of a diazonium salt, a diaryl iodonium salt, a triaryl sulfonium salt, an alkyl sulfonium salt, an iron arene salt, a sulfonyloxy ketone or a triaryl siloxane ether; And / or, the cationic thermal initiator includes one or a combination of multiple of antimonates, phosphates, alkylammonium salts, aryldiazonium salts or onium salts.

6. Use of the degradable epoxy resin composition according to any one of claims 1 to 5 in the preparation of wind power composite materials, electronic consumer products, electronic packaging or electrical resins.

7. A degradable epoxy resin cured product, characterized in that: The degradable epoxy resin cured product is formed by thermal curing or photocuring of the degradable epoxy resin composition according to any one of claims 1 to 5.

8. The degradable epoxy resin cured product according to claim 7, characterized in that: The thermal curing method comprises: curing the degradable epoxy resin composition at a temperature of 50 to 100° C. for 3 to 6 hours; And / or, the photocuring method comprises: irradiating the degradable epoxy resin composition under ultraviolet light for 5 to 10 minutes; And / or, the degradable epoxy resin cured material can be degraded in an alkaline aqueous solution or seawater; in an alkaline aqueous solution at 25 to 100° C., the degradation rate of the degradable epoxy resin cured material within 2 to 48 hours is ≥ 99%; in seawater at 25° C., the degradation rate of the degradable epoxy resin cured material within 300 to 900 days is ≥ 99%; And / or, the glass transition temperature of the degradable epoxy resin cured product is 50-150°C, the tensile strength is 50-110 MPa, and the unnotched impact strength is 30-60 kJ / m 2 .

9. A device having a degradable structure, characterized in that: The degradable structure of the device comprises the degradable epoxy resin cured product according to claim 7 or 8.

10. A method for degrading a degradable epoxy resin cured product, characterized in that: include: The degradable epoxy resin cured product according to claim 7 or 8 is immersed in an alkaline solution to degrade it, or is placed in seawater for natural degradation; Preferably, the pH value of the alkaline solution is 9 to 14; Preferably, the soaking time in the alkaline solution is 2 to 48 hours; Preferably, the temperature of the alkaline solution is above 25°C, preferably 25-100°C.

Citation Information

Patent Citations

  • Polyester elastomer and preparation method thereof

    CN105524261A

  • High-strength and high-toughness easily-degradable epoxy resin composition, preparation method and application

    CN117820811A

  • Epoxy resin composition, cured product, sealing material, and adhesive

    CN118302470A